Reasons for loss to follow-up in antiretroviral treatment programs in South Africa - Bärnighausen, Till (HIV therapy, 2008)
Evaluation of: Maskew M, MacPhail P, Menezes C, Rubel D: Lost to follow-up: contributing factors and challenges in South African patients on antiretroviral therapy. S. Afr. Med. J. 97(9), 853-857 (2007); and Dalal RP, MacPhail C, Mqhayi M et al.: Characteristics and outcomes of adult patients lost to follow-up at an antiretroviral treatment clinic in Johannesburg, South Africa. J. Acquir. Immune Defic. Syndr. 47(1), 101-107 (2008). For evaluation and management of antiretroviral treatment programs it is important to understand the reasons for loss to follow-up. The authors of two studies conducted in two large antiretroviral treatment programs in public hospitals in the city of Johannesburg, South Africa, identified patients who were lost to follow-up through chart reviews (154 of 5821 patients in the first study and 267 of 1631 patients in the second study) and then attempted to trace patients in order to ascertain the reasons for loss to follow-up. In both studies, large proportions of patients (55 and 35%) could not be traced because contact information was either missing or incorrect. Of patients who were successfully traced, large proportions were found to have died (27% in the first study and 48% in the second study) or to have continued antiretroviral treatment (ART) at other facilities (14 and 17%). A number of reasons for loss to follow-up were common in only one of the two studies (financial difficulty, lack of knowledge that ART needs to be lifelong, and hospitalization or illness). Among the patients who were found to have died, CD4 counts at enrollment were low (mean [standard deviation; SD] CD4 count of 62 [66] cells/µl in the first study; median [interquartile range; IQR] CD4 count of 33 [9-111] cells/µl in the second study) and duration of ART was short (mean [SD] duration of 56 [42] days; median [IQR] duration of 80 [28-140] days).